Strong-weak dual interface engineered electrocatalyst for large current density hydrogen evolution reaction - Shaorou Ke; Ruiyu Mi; Xin Min; Xinyu Zhu; Congyi Wu; Xin Li; Bozhi Yang; Xiaowen Wu; Yangai Liu; Zhaohui Huang; Minghao Fang (Communications Materials)
Abstract Supported nanocatalysts are crucial for hydrogen production, yet their activity and stability are challenging to manage due to complex metal-support interfaces. Herein, we design Pt@ anatase&rutile-TiO2 with a strong-weak dual interface by modifying TiO2 using high-energy ball milling and in-situ reduction to vary surface energies. Experiments and density functional theory calculations reveal that the strong Pt-anatase TiO2 interface enhances hydrogen adsorption. In contrast, the weak Pt-rutile TiO2 interface facilitates hydrogen desorption, simultaneously preventing Pt agglomeration and increasing reaction rate. As a result, the tailored catalyst has a 529.3 mV overpotential at 1000 mA cm−2 in 0.5 M H2SO4, 0.69 times less than commercial Pt/C. It also possesses 8.8 times the mass activity of commercial Pt/C and maintains a low overpotential after 2000 cyclic voltammetry cycles, suggesting high activity and stability. This strong-weak dual interface engineering strategy shows potential for overall water splitting and proton exchange membrane water electrolyzer, advancing the design of efficient supported nanocatalysts.